A local structure of null hypersurfaces of $\mathbb{R}_{1}^{n+1}$ - Ssekajja, Samuel (My University, 2019)
In the present paper, we characterize constant mean curvature and scalar curvature null hypersurfaces of $\mathbb{R}_{1}^{n+1}$. Locally, such hypersurfaces are a product of a null curve and generalized cylinders.
Keywords: Isoparametric null hypersurfaces; Null hypersurfaces; Screen conformal hypersurfaces